Effect of maturity at harvest on yield, composition, and feeding value of hybrid forage sorghum silages - Dickerson, J.; Bolsen, K.; Hamma, S.; Hoover, J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Results from three trials showed the diversity among forage sorghum hybrids for both agronomic and nutritive characteristics. Later maturing and nonheading hybrids produced silages with low dry matter (DM) contents, low pH values, high levels of fermentation acids, and low voluntary intakes. Earlier maturing and moderate grain-producing hybrids, but their silages had high DM contents and higher voluntary intakes. Stage of maturity at harvest had surprisingly little influence on silage chemical composition, intake, or digestibility.
Keywords: Beef; Maturity; Yield; Feed value; Forage sorghum silages